2013
DOI: 10.1080/00018732.2013.808047
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nanoscience: from nano-solids in plasmas to nano-plasmas in solids

Abstract: The unique plasma-specific features and physical phenomena in the organization of nanoscale solid-state systems in a broad range of elemental composition, structure, and dimensionality are critically reviewed. These effects lead to the possibility to localize and control energy and matter at nanoscales and to produce self-organized nano-solids with highly unusual and superior properties. A unifying conceptual framework based on the control of production, transport, and self-organization of precursor species is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
399
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 498 publications
(404 citation statements)
references
References 398 publications
(614 reference statements)
3
399
0
2
Order By: Relevance
“…Plasmas have recently shown a unique ability to selectively functionalize the surface of carbon-based materials with controllable and graded intensity and depth. 32,33 In particular, the low-energy ions and electrons in atmospheric-pressure DBD plasma may be ideal for grafting a variety of functional groups at the outmost regions over a large area without damaging the structure.…”
Section: Improved Cyclic Stability Through Plasma Treatmentmentioning
confidence: 99%
“…Plasmas have recently shown a unique ability to selectively functionalize the surface of carbon-based materials with controllable and graded intensity and depth. 32,33 In particular, the low-energy ions and electrons in atmospheric-pressure DBD plasma may be ideal for grafting a variety of functional groups at the outmost regions over a large area without damaging the structure.…”
Section: Improved Cyclic Stability Through Plasma Treatmentmentioning
confidence: 99%
“…Plasmas can ensure simultaneously high temperatures, highly reactive environment-electrons, ions, free radicals, energetic photons (UV radiation). For example, it has been shown that in plasma-enhanced chemical vapor deposition [1,3,5,7,9,10] a high level of control over material fluxes, heating and concomitantly the structure and properties of formulated materials can be achieved. This method makes use of a substrate inserted in a low-pressure plasma environment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the synthesis and growth of carbon nanostructures proceed via surface reaction and therefore depend on surface conditions. The review of the current status of the plasmabased fabrication of carbon nanostructures and in particular of graphene can be found elsewhere [1,3,5,9,10]. Different plasma sources have been tested using various precursors (methane, alcohols, etc) for graphene synthesis [3,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations